Race, class, and gender intersections and inequalities - Andersen, Margaret L.; Hill Collins, Patricia (Cengage, 2020)
Featuring an accessible and diverse collection of more than 50 writings by a variety of scholars, this anthology demonstrates how the complex intersection of people's race, class, gender and sexuality shapes their experiences. Co-edited by two leading authorities, Race, class, and gender is a classic work that has helped define the field of intersectionality studies. Updated to reflect the most current research and recent societal events, the readings in the 10th edition are especially timely, covering immigration and refugees, myths about immigrant crime, growing inequality, the role of social media in social movement mobilization, health care inequality, and more--equipping readers with a multidimensional perspective on today's social issues. Andersen and Hill Collins begin each section with in-depth introductions to provide an analytical framework for understanding social inequality.